Proceedings of International Symposium on Oilfield Chemistry 2007
DOI: 10.2523/106375-ms
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Gravitational Gradient in a Deepwater Reservoir as Determined by Downhole Fluid Analysis

Abstract: fax 01-972-952-9435. AbstractThe fluids in large reservoirs can be in equilibrium -especially if conditions conducive to convective mixing prevail. A large vertical column of reservoir hydrocarbons offers a unique laboratory to investigate potential gravitational grading. Asphaltenes are known to exist in crude oils as a colloidal suspension, but which had not been well characterized in the laboratory until recently. In this paper, we review a gravitational gradient of asphaltenes in a reservoir and a simple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…One sample appeared to have lost some asphaltene content in the laboratory analysis compared to DFA. 7 The results confirmed that same trends observed in the downhole live fluid data were duplicated in the dead oil samples, i.e. Fortunately a second sample bottle in the same sand was available with the original concentration of asphaltenes.…”
Section: Chain Of Custodysupporting
confidence: 80%
See 1 more Smart Citation
“…One sample appeared to have lost some asphaltene content in the laboratory analysis compared to DFA. 7 The results confirmed that same trends observed in the downhole live fluid data were duplicated in the dead oil samples, i.e. Fortunately a second sample bottle in the same sand was available with the original concentration of asphaltenes.…”
Section: Chain Of Custodysupporting
confidence: 80%
“…7 This asphaltene concentration gradient was used to predict DFA data throughout the field to confirm reservoir connectivity, thereby reducing the key risk factor in the Tahiti development. This fluids map is then used to predict all upcoming DFA log data before a new well is drilled.…”
Section: Introductionmentioning
confidence: 99%
“…[4,22,23] The FHZ EoS has been used successfully to model heavy end gradients in reservoirs for fluids ranging from nearly colorless condensates to heavy oils. [4] For different reservoir fluids, different species (with diameters listed in nanometers) form the asphaltene or heavy end gradient: for the nearly colorless condensates, it is the colored resins (~1nm); [25] for a light oil, it is the asphaltenes molecules (~1.5nm); [26] for black oils, it is the asphaltene nanoaggregate (~2nm); [27,28] and for heavy oil it is the asphaltene cluster (~5nm). [3,29,30] The relatively large asphaltene clusters produce very large asphaltene gradients, with asphaltene concentration doubling every 20 meters of height in the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 14 shows the huge range of crude oil coloration, in the visible and extending into the NIR; the coloration is closely related to the asphaltene content. [20] Close examination of the spectral region at 1700nm can be used to analyze dissolved methane enabling GOR measurements as shown in Fig. 15.…”
Section: Downhole Fluid Analysis (Dfa)mentioning
confidence: 99%